Dockless bike-sharing’s impact on mode substitution and influential factors: Evidence from Beijing, China - Zheyan Chen; Dea van Lierop; Dick Ettema (Journal of Transport and Land Use)
As a newly emerged bike-sharing system, dockless bike-sharing has the potential to positively influence urban mobility by encouraging active cycling and drawing users from car, public transit and walking. However, scant empirical research explores the extent to which dockless bike-sharing replaces other travel modes for different travel purposes. There is a lack of knowledge about how dockless bike-sharing users’ personal characteristics and neighborhood environment features influence their mode substitution behaviors. Using survey data collected from residents in Beijing and geodata of land use and public transit, we conduct four multinomial logistic models to explore potential mode-substitution behaviors influenced by dockless bike-sharing for four travel purposes: work or education commuting, sports and leisure, grocery shopping, and recreational activities such as shopping, eating and drinking. The results indicate that, for the majority of respondents, dockless bike-sharing systems potentially substitute for walking or public transit. In addition, our analysis of travel attitudes points out that dockless bike-sharing not only attracts bicycle lovers but also users with a preference or positive attitude toward other travel modes. The positive association between the length of bicycle paths and the likelihood of potentially replacing public transit or motorized vehicles by dockless bike-sharing also reveals that the cycling infrastructure of residential neighborhood could be an important facilitator for users of public transit and motorized vehicles to switch to dockless bike-sharing systems.